1978
DOI: 10.1530/jrf.0.0530023
|View full text |Cite
|
Sign up to set email alerts
|

The role of histamine in implantation in the rabbit

Abstract: When disodium cromoglycate, an inhibitor of histamine release, was instilled into the uterine lumen on Days 5 or 6 of pregnancy, the number of blastocysts implanting was significantly (P less than 0.002) reduced. Simultaneous instillation of histamine and disodium cromoglycate prevented the effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1983
1983
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…52 Earlier observations suggested that uterine mast cells were the possible source of histamine, and its release from mast cells by estrogen was important for implantation. 53,56 Histamine works via at least four histamine receptor subtypes (H 1 -H 4 ), 57-59 and blocking of both H 1 and H 2 receptors was shown to interfere with implantation in rats. 55 Furthermore, a histamine antagonist pyrathiazine or an inhibitor of histidine decarboxylase (HDC) was shown to interfere with implantation when instilled into the uterine lumens of rats and rabbits.…”
Section: Window Of Implantationmentioning
confidence: 99%
“…52 Earlier observations suggested that uterine mast cells were the possible source of histamine, and its release from mast cells by estrogen was important for implantation. 53,56 Histamine works via at least four histamine receptor subtypes (H 1 -H 4 ), 57-59 and blocking of both H 1 and H 2 receptors was shown to interfere with implantation in rats. 55 Furthermore, a histamine antagonist pyrathiazine or an inhibitor of histidine decarboxylase (HDC) was shown to interfere with implantation when instilled into the uterine lumens of rats and rabbits.…”
Section: Window Of Implantationmentioning
confidence: 99%
“…He identifi ed that blue bands were apparent on day 5 of pregnancy in mice and are one of the earliest visible signs of implantation (Psychoyos 1961 ). In this respect, histamine, a vascular permeability factor, was considered relevant for implantation in rodents and rabbits (Shelesnyak 1952 ;Dey et al 1978Dey et al , 1979, again suggesting proinfl ammatory responses during implantation. These studies were then followed by the identifi cation of crucial roles for cyclooxygenase (Cox1 and Cox2)-derived prostaglandins in female reproduction (Pakrasi et al 1983 ;Kennedy et al 2007 ).…”
Section: Molecular Signature For Attachment Reaction and Implantationmentioning
confidence: 99%
“…Implantation in rabbits is also adversely affected by the intrauterine instillation of disodium cromoglycate, an inhibitor of histamine release from mast cells (Dey et al 1978). In rats with delayed implantation, concomitant administration of histamine and oestradiol reduces the amount of oestradiol required to bring about implantation (Johnson and Dey 1980).…”
Section: Histamine As the Signalmentioning
confidence: 99%